Efficient smart garbage management system using IOT technique - K. Vijaya Sri, Dr; Vamsi Krishna, R; J. K. Surya, M; Venkatesh Babu, D (International Journal of Engineering and Technology, 2018)
The Proposed Smart Waste Management System is to manage the waste with the help of smart sensors along with data fill-level indication, the garbage existence all over dustbin, containers and garbage bins foul smelling conditions will be sent as an alert to the registered / specified workers as an message. An accredited mobile number that are working in Waste Management Centres gathers fill-level. The remaining of multiple containers information transmitted where it placed all over the marginal location. Gathered data from the above process, utilised for gathering the garbage in a systematic plan and a route-map. Used communication devices in the implemented project transmitted the data from garbage bin to the authorised persons. An eight bit microcontroller i.e Atmega328P regulated the total functionality of this system. This narration demonstrates an effective design of IoT gateway which is utilised for offering the â€œsmart waste management systemâ€ framework.Â Â